Factors Associated With Asthma Control in 121 Preschool Children - Leiria-Pinto, P (2021)
Background: Data on risk factors for uncontrolled asthma in preschool children are controversial. Objective: This study aims to explore the association between clinical and functional parameters and the lack of asthma control in preschool children. Methods: Children aged 3-5 years with asthma and healthy controls were recruited. A questionnaire was used to identify potential risk factors for uncontrolled asthma, as defined by the Global INitiative for Asthma criteria. Lung function and bronchial reversibility were evaluated through impulse oscillometry and spirometry. Adjusted odds ratios were estimated based on multivariable generalized additive regression models. The discriminative ability of the models was measured by the area under the receiver operating characteristic curve (AUC). Results: The study population comprised 121 children (107 with asthma and 14 healthy controls). Fifty-three patients (50%) had uncontrolled asthma. After adjustment, the variables associated with an increased risk of lack of control were as follows: “More than 3 flare-ups in the last 12 months”, “Moderate to severe rhinitis”, and “Relative variation in postbronchodilator FVC and FEV1”. The AUC of the final models that included variation in FVC or FEV1 were 0.82 and 0.81, respectively. The R5-20, R5-20%, and AX z-score values of the healthy group were lower than those of children with asthma. Conclusion: In preschool children, clinical and functional parameters are associated with uncontrolled asthma. More studies are needed to confirm the usefulness of impulse oscillometry.